ASSESSING MAFINDO’S COMMUNICATION APPROACH IN THE TULAR NALAR PROGRAM: A STUDY OF DIGITAL LITERACY FOR THE ELDERLY IN BANDA ACEH - Syarifah Dhamratus Shiddiqah; Febri Nurrahmi; Nasya Bahfen; Tanzir Masykar (JURNAL ILMU SOSIAL, 2025)
Internet use in Indonesia continues to increase across all age groups, including the elderly. However, limited digital skills make the elderly particularly vulnerable to hoaxes and digital crimes. In Aceh, this issue is especially concerning, as the province was identified among the top three regions with the highest hoax dissemination in 2019. In response, the Indonesian Anti-Slander Society (Mafindo), through its Tular Nalar program, aims to provide digital literacy education to vulnerable groups, including the elderly. This study explores the communication strategy employed by Mafindo Aceh in implementing the Tular Nalar Lansia program in Aceh. Guided by Charles Berger’s Planning Theory and Hafied Cangara’s communication strategy model, the study adopts a qualitative case study approach to offer a contextually relevant analysis. Data were gathered through interviews with the Mafindo Aceh Coordinator, two facilitators, and three elderly participants, along with non-participant observations and document analysis. Findings reveal that although the program was implemented in a structured manner, several weaknesses remain, such as the lack of localized research, inadequate participant selection, and limited evaluation mechanisms. The study underscores the need for communication strategies that are inclusive, culturally sensitive, and tailored to the elderly’s abilities to enhance the impact of digital literacy initiatives.